2021
DOI: 10.3389/fcell.2020.603815
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Integrated Analysis Revealed Functions of lncRNA–miRNA–mRNA Interaction in Growth of Intermuscular Bones in Megalobrama amblycephala

Abstract: Intermuscular bone (IB) occurs in the myosepta of teleosts. Its existence has an adverse influence on the edible and economic value of fish, especially for aquaculture species belonging to Cypriniformes. The growth mechanism of IBs is quite lacking. In this study, we firstly used single molecular real-time sequencing (SMRT) technology to improve the draft genome annotation and full characterization of the transcriptome for one typical aquaculture species, blunt snout bream (Megalobrama amblycephala). The long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 77 publications
3
13
0
Order By: Relevance
“…LncRNAs can also interact with microRNAs (miRNAs), another type of ncRNAs involved in posttranscriptional regulation of protein-coding genes by mRNA cleavage, translational repression, or mRNA destabilization [21]. LncRNAs can act as miRNAs precursors or as miRNAs sponges, thus altering their regulatory effect on mRNAs and introducing an additional layer of complexity in the miRNA-target interaction network [21][22][23]. All the specific interactions of lncRNAs are sometimes based on sequence complementarity, but it is suggested that, in many cases, the lncRNAs' function is defined by their three-dimensional structure [24].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs can also interact with microRNAs (miRNAs), another type of ncRNAs involved in posttranscriptional regulation of protein-coding genes by mRNA cleavage, translational repression, or mRNA destabilization [21]. LncRNAs can act as miRNAs precursors or as miRNAs sponges, thus altering their regulatory effect on mRNAs and introducing an additional layer of complexity in the miRNA-target interaction network [21][22][23]. All the specific interactions of lncRNAs are sometimes based on sequence complementarity, but it is suggested that, in many cases, the lncRNAs' function is defined by their three-dimensional structure [24].…”
Section: Introductionmentioning
confidence: 99%
“…These results were compared with reported AS values for other animal species from studies that also used SUPPA on Iso-Seq reads. Results reported were compiled for the zebrafish ( Danio rerio ) (Nudelman et al, 2018), the goldfish ( Carassius auratus auratus ) (Gan et al, 2021), the Wuchang bream ( Megalobrama amblycephala ) (Chen et al, 2021), the whiteleg shrimp ( Litopenaeus vannamei ) (X. Zhang et al, 2019), and the cave nectar bat ( Eonycteris spelaea ) (Wen et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…These results were compared with reported AS values for other animal species from studies that also used SUPPA on Iso-Seq reads. Results reported were compiled for the zebrafish ( Danio rerio ) ( Nudelman et al ., 2018 ), the goldfish ( Carassius auratus auratus ) ( Gan et al ., 2021 ), the Wuchang bream ( Megalobrama amblycephala ) ( Chen et al ., 2021 ), the whiteleg shrimp ( Litopenaeus vannamei ) ( Zhang et al ., 2019 ), and the cave nectar bat ( Eonycteris spelaea ) ( Wen et al ., 2018 ).…”
Section: Methodsmentioning
confidence: 99%